KAJIAN YURIDIS TENTANG KEBERADAAN PERGURUAN TINGGI NEGERI BADAN HUKUM MILIK NEGARA DALAM UNDANG-UNDANG SISTEM PENDIDIKAN NASIONAL - Rianti, * (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2011)
This research aims to analyze and expose how the position of the College of law in Agency-owned Country laws and regulations in these rights are examined from the legislation of the national education system. It also seeks to analyze and expose the juridical effects of the verdict of the Constitutional Court No. 11-14-21-126-136/PUU-VII/2009 against Universities State-owned legal entity. Establishment of universities in the form of a State-owned legal entity is as an attempt to provide unhampered to College for more independent in managing the activities of the Organization of the education in the institution. Lightness of being given to the College would not escape from the framework of the national education system. In order to realize the independence of such an ACT, namely Act No. BHP 9 2003. In the Act that the units are arranged in the shape of Education Education legal entity. The application of the concept of legal entities give rise to various kinds of Education turns pro cons. The concept of a legal entity described as if the Government let go of responsibility in the field of education. The concept of legal entities concerned about making education unit became a non-profit institution. In the end the Constitutional Court decided BHP LAW has no legal binding force. The position of the BHMN if examined through the Sisdiknas Article 53 is a body of legal education. Because it is considered as one legal entity, then the PTN BHMN as supporters of rights and obligations. The concept of PTN BHMN as one legal entity principled profit. As a legal entity has the will and PTN BHMN which will be formulated in the vision and mission of higher education institutions each of which surely should not be contrary to the purpose of national education which have been outlined in the ACT Sisdiknas.Keywords: College State-owned legal entity, legal entities, Education Law system of national education, the Constitutional Court.